Exploring Foreign Language Teaching Anxiety: A Case Study of Pre-Service Teachers Professional Education Program - Nafiah, Elmiatun (Jurnal Pendidikan Humaniora, 2024)
Pre-service teachers face profound worries regarding Foreign Language Teaching Anxiety (FLTA), especially in the Indonesian context. This study investigates the determinants of FLTA, the methods teachers employ for dealing with anxiety, and the contribution of the Teacher Education Program (PPG) to alleviating the stress associated with teaching. Two in-service teachers who completed the PPG program were interviewed using a case study design, and the material was examined through thematic analysis. The data is presented based on the Foreign Language Teaching Anxiety Scale proposed by Horwitz (1996). According to the survey, the primary contributors to anxiety are factors including students' lack of enthusiasm and personal perceptions of their language proficiency. Teachers use various strategies to combat stress such as modifying lesson plans and raising students' awareness. PPG considerably decreases anxiety by improving pedagogical abilities and influencing instructors' perspectives. The results shed light on FLTA in the Indonesian educational setting resulting in implications for programs that prepare future teachers along with strategies for diminishing pre-service teachers' anxiety.